Mineralization of Hydrochlorothiazide using Hydrogen Peroxide in Subcritical Water - Erdal Yabalak (Journal of the Turkish Chemical Society, Section A: Chemistry, 2018)
In this paper, we investigated the mineralization of hydrochlorothiazide, a diuretic drug which is used for the treatment of hypertension, using H2O2 as the oxidizing agent in subcritical water as a medium. Response surface methodology was applied to optimize experimental parameters such as temperature, treatment time, and concentration of the oxidizing agent. 85.22% of TOC removal was obtained at 403 K, 80 mM of hydrogen peroxide and 147.3 min. The reliability of the performed method was evaluated by ANOVA and the theoretical equation of TOC removal of hydrochlorothiazide was proposed. F and p values of the model were determined as 62.88 and lower than 0.0001, respectively.